Adrenal obliteration by balloon-occluded retrograde venous ethanol injection in a swine model. Issue 6 (2nd November 2017) - Inoue, Akitoshi; Ohta, Shinichi; Nitta, Norihisa; Tsuboi, Shizuka; Sonoda, Akinaga; Tomozawa, Yuki; Watanabe, Shobu; Mukaisho, Kenichi; Murata, Kiyoshi
Abstract: Purpose: To evaluate the effects of adrenal obliteration by balloon-occluded retrograde venous ethanol injection. Material and methods: We inserted a micro-balloon catheter into the left adrenal vein of six pigs and retrogradely injected absolute ethanol (0.06 ml/kg) under balloon occlusion. Two pigs were sacrificed on day 3, 7, and 14 after the procedure, respectively. We evaluated adrenal cortical and medullary hormones of the left renal vein, venograms, magnetic resonance imaging scans obtained before and after the procedure, autopsy and microscopic findings, and the weight of the bilateral adrenal glands. Results: The hormone levels were extremely high on day 3 after the procedure. Post-procedure, partially-enhanced parenchyma and shaggy veins were observed. On the post-mortem examination, the left adrenal glands showed hemorrhage and adhesion on the third and seventh day and fatty proliferation 14 days after the procedure. Microscopic examination revealed hemorrhagic necrosis on day 3, inflammatory cell infiltration on day 7, and partial fibrosis 14 days after the procedure. The weight of the left adrenal gland on day 14 was lower than that of the right gland. Conclusions: This procedure elicited partial adrenal infarction with a high catecholamine concentration in the left renal vein.